In situ conservation and landscape genetics in forest species - Martín L.M.; Herrera M.A; Martín M.A (Journal of Natural Resources and Development, 2012)
Conservation of forest genetic resources is essential for sustaining the environmental and productive values of forests. One of the environmental values is the conservation of the diversity that is assessed through the amount of genetic diversity stored by forests, their structure and dynamics. The current need for forest conservation and management has driven a rapid expansion of landscape genetics discipline that combines tools from molecular genetics, landscape ecology and spatial statistics and is decisive for improving not only ecological knowledge but also for properly managing population genetic resources. The objective of this study is to show the way to establish the safeguard of genetic diversity through this approach using the results obtained in sweet chestnut (Castanea sativa Mill.) that has provided a better understanding on the species genetic resources. In this respect, we will show how the information provided by different types of molecular markers (genomic and genic) offer more accurate indication on the distribution of the genetic diversity among and within populations assuming different evolutionary drivers.